Tłumaczenia niektórych tekstów współczesnej prozy polskiej na język czeski — przyczynek do dialogu kultur - Pavera, Libor (Przekłady Literatur Słowiańskich, 2011)
Translations of Certain Contemporary Polish Prose Works into Czech — a Contribution to the Dialogue between Cultures In his paper, the author deals with the topic of rendering the contemporary Polish literature, created after the year 1989, into the Czech language. He reminds the reader of certain facts from the literary life of the last 20 years and analyses certain texts of the contemporary Polish prose which were translated into Czech. It is not guaranteed that the outcome of numerous translations will be ever printed. What is more, Polish literature is not systematically published in the Czech Republic. On the other hand, the translations which have been published may show a Czech reader Polish people and the contemporary Poland in a different light than it was done earlier. The researcher quotes D. Maslowska’s prose, who introduces a Czech reader to the subculture of „dreserzy”(„dresiarze”), which requires a translator to find an adequate style and language in order to render the whole context into the target language. Another approach to the issue of shattering the image of Poles has been taken by J. Witkowski, who looks at the specific gay community in his texts. Finally, in the last example, the author shows how M. Szczygiel, a Pole, views the Czech history in the XXth century (the prose Gottland). The author also mentions the fact that there have been analogical processes in both literary cultures (subject matter, selection of means of literature, etc.).